Exploring causal correlations between circulating cytokines and atopic dermatitis: a bidirectional two-sample Mendelian randomization study - Zhenquan Xuan; Zhenquan Xuan; Zhenquan Xuan; Xuanyi Chen; Xuanyi Chen; Xuanyi Chen; Weinan Zhou; Weinan Zhou; Weinan Zhou; Yihang Shen; Yihang Shen; Yihang Shen; et al. (Frontiers in Immunology, 2024)
ObjectivesNumerous observational studies have reported associations between circulating cytokines and atopic dermatitis (AD); however, the causal relationships between them remain unclear. To explore the causal correlations and direction of causal effects between AD and levels of 91 circulating cytokines.MethodsTwo-sample Mendelian randomization (MR) analyses were conducted to examine the causal relationships between 91 circulating cytokines and AD using summary statistics from genome-wide association studies (GWAS). Reverse MR analyses were performed to investigate reverse causation. Pleiotropy and heterogeneity tests were conducted to assess the robustness of the findings. Additional transcriptome database and clinical peripheral blood mononuclear cells (PBMCs) samples were utilized to validate the results of MR analyses.ResultsLevels of interleukin (IL)-13, IL-18 Receptor 1, Tumor necrosis factor ligand superfamily member 14 (TNFSF14), TNF-related activation-induced cytokine (TRANCE), C-X-C motif chemokine (CXCL)11, IL-33, TNF-beta and CD5 were suggestively associated with the risk of AD (odds ratio, OR: 1.202, 95% CI: 1.018–1.422, p = 0.030; OR: 1.029, 95% CI: 1.029–1.157, p = 0.004; OR: 1.159, 95% CI: 1.018–1.320, p = 0.026; OR: 1.111, 95% CI: 1.016–1.214, p = 0.020; OR: 0.878, 95% CI: 0.783–0.984, p = 0.025; OR: 0.809, 95% CI: 0.661–0.991, p = 0.041; OR: 0.945, 95% CI: 0.896–0.997, p = 0.038; OR: 0.764, 95% CI: 0.652–0.895, p = 8.26e-04). In addition, levels of cytokines including Axin-1, CXCL5, CXCL10, Oncostatin-M (OSM), Sulfotransferase 1A1 (SULT1A1) and TNFSF14 were suggested to be consequences of AD (Beta: -0.080, p = 0.016; Beta: -0.062, p = 0.036; Beta: -0.066, p = 0.049; Beta: -0.073, p = 0.013; Beta: -0.089, p = 0.008; Beta: -0.079, p = 0.031). IL-13, IL-18R1, TNFSF14, and TRANCE were upregulated in both lesional skin biopsies and PBMCs from AD patients.ConclusionThe study indicates that several cytokines, including IL-13, IL-18R1, TNFSF14, TRANCE, CXCL11, IL-33, TNF-beta, and CD5, are upstream of AD development, whereas a few circulating cytokines are potentially downstream in the development of AD.